(untitled) (Journal of Pharmaceutical Negative Results, 2017)
Data are lacking on the incidence of adverse effects ofdonations made with modern apheresis instruments.[1]Hence, we analyzed a total of 90 plateletpheresis proceduresover a period of 3 months (September 2015 toNovember 2015) on Trima Accel cell separator. Donorswere selected as per the set criteria for single donor plateletpreparation according to the AABB guidelines. All the 90donors were male with mean age 30.5 years and mean weight77.3 kg [Table 1]. Of these 90 donors, 23 donors (25.6%)developed some adverse events (AE) [Table 2].